THE CHALLENGES OF HOSPITAL INFORMATION SYSTEM IMPLEMENTATION: A CASE STUDY OF A PUBLIC HOSPITAL IN INDONESIA - Fabianus Herman Kurnia Agung Widiyanto; Aris Widayati (Sanata Dharma University, 2021)
The Indonesian government has mandated using the Hospital Information System (HIS) since 2013. Until now, not all hospitals in Indonesia have implemented HIS, however. Some barriers have prevented them from applying HIS. This study explores the opportunities and barriers regarding implementing the Hospital Information System (HIS) in Indonesia through a public hospital case study. This study applied a qualitative approach. The approach used interviews to gather data using a pre-tested interview guideline. The guideline used several constructs to structure the questions, i.e., predisposing, enabling, reinforcing, barrier, and projected behavior. Participants were different types of HIS users in the studied hospital, i.e., physician, nurse, pharmacist, administrators, laboratory personnel, and Information Technology (IT) personnel. Data were transcribed verbatim and analyzed thematically. The interviews involved twenty-one participants. Nine themes describe HIS implementation challenges in this case study, i.e., familiarity, flexibility, empowerment, discipline, facilities, data sharing, quality assurance, pragmatism, and capacity building. Pragmatism could be a barrier, while the other values would be opportunities. These challenges are promising in guiding HIS implementation success. The values found in this study convince that HIS implementation in Indonesia is promising. Those challenges are required to be taken into account to implement HIS successfully.